OTOMATISASI PENGATURAN SUHU AIR PADA PETERNAKAN PEMBUDIDAYA IKAN NILA - Rivaldi Rasqi Al Zahabi; Angga wicaksana, Fiqih Assidiq Ramadhan, Paduloh (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
In tilapia cultivation, the optimal temperature for growing tilapia in ponds is around 25°C – 30°C. Unstable changes in water temperature in tilapia ponds can cause seed death, therefore it is necessary to monitor regularly to maintain stable water temperature. Ways to maintain stable water temperature in this range include using a heater with normal limits. This tool was created to automate water temperature monitoring using an Arduino Uno pH sensor, LM35 as a temperature sensor and controlling water levels using the HCSR-04 ultrasound sensor. The output of water temperature measurements on the LCD screen and monitor is in the form of numbers, making it easier for tilapia fish farming to monitor temperature conditions. fish pond water